(untitled) (Physical Education, Health and Social Sciences, 2026)
Hypothermia occurs when body temperature drops below 36°C, deviating from the normal range of 36-38°C. Unintentional hypothermia is a prevalent complication of general anesthesia, despite precautions to maintain core temperature. Anesthesia disrupts the body’s thermoregulatory system, leading to various postoperative issues, including cardiovascular problems, bleeding complications, and impaired drug metabolism. Factors contributing to postoperative hypothermia include anesthetic type, operating room temperature, surgical procedure, IV fluid temperature, and duration of anesthesia and surgery.A cross-sectional observational study was conducted at Mardan Medical Complex using a questionnaire. Informed consent was obtained, and data was analyzed with SPSS version 31.The primary objective of this study was to assess the incidence and identify potential predictors of postoperative hypothermia among 333 patients who underwent various surgical procedures. Based on the data collected, it was observed that 27.93% of the patients developed hypothermia in the postoperative period. This notable incidence underscores the clinical importance of recognizing and addressing the factors contributing to postoperative hypothermia to improve patient outcomes and ensure safer perioperative careThis study explored the incidence and associated risk factors of postoperative hypothermia in patients undergoing anesthesia. The results revealed a notable correlation between increased incidence of postoperative hypothermia and factors such as female gender and older age. These findings emphasize the need for heightened perioperative monitoring and preventive strategies in high-risk patient groups to minimize the occurrence of hypothermia and its related complications.